The Effect of Orally Administered Lactobacillus rhamnosus as "Systemic Probiotics" on C-Reactive Protein Levels and Wound Healing of Oral Mucosa in Rabbits - Rashad Sinan Attarbashi; Faehaa Azher Al-Mashhadane; Rasha Farouk Albannaa (University of Mosul, College of Dentistry, 2024)
Aims: This study investigates the beneficial role of Lactobacillus rhamnosus in oral wound healing. Materials and methods: Twenty-five rabbits were divided into three main groups; The First was the Negative Control group(group I) with five rabbits, these had neither surgery nor treatment. The second was the Positive control group(group II) with ten rabbits, these had an incisional cut of 1cm in their buccal mucosa but none had received any treatment. The rabbits in this group were subdivided into two subgroups (a and b) with five animals each according to the time of euthanasia, as explained below. The third was the treatment group (group III) with ten rabbits. These all had the same oral incision and received probiotic drops (VITRON® Farma, Turkey); an already prepared solution containing Lactobacillus rhamnosus, 5 oral drops (0.25 ml)/kg to be swallowed once daily starting from the first day of study till the day of euthanizing. Animals in this group were also subdivided equally into a and b subgroups according to the time of euthanasia. The rabbits from group I and subgroups IIa and IIIa were euthanized on the third-day post-surgery. All other rabbits from subgroups IIb and IIIb were euthanized on the seventh-day post-surgery. Serum samples were collected and mucosal tissue at wound sites was excised for histological analysis. Results: The serum levels of C-reactive protein (CRP) in the third-day groups of the study indicated a highly significant difference (P ≤0.001), as well as between the groups on the seventh day which also showed a noticeable decrease in the concentration of these cytokines. A microscopic inspection in the Positive Control group after three days revealed a wound with inflammatory exudate, fibrin deposition, and destruction of the epithelium layer of mucosa with slight re-epithelialization. The seventh-day tissue of the positive control group showed highly inflammatory cell infiltration, fibrin deposition, reepithelialization, and minimal granulation tissue formation. In contrast, the treatment group's mucosal wounds on three postsurgical days showed a wound site with little inflammatory exudate, early signs of reepithelialization, and well-formed granulation tissue, while on day seven showed a wound site with no inflammatory exudate, well-developed re-epithelialization, well granulation tissue formation and signs of angiogenesis. Conclusion: Systemic probiotic Lactobacillus rhamnosus enhanced the wound healing of oral mucosa in rabbits.